2018
DOI: 10.1103/physrevb.97.144505
|View full text |Cite
|
Sign up to set email alerts
|

Fulde-Ferrell-Larkin-Ovchinnikov superconductivity in the layered organic superconductor β(BEDTTTF)4[(H3

Abstract: Resistance and magnetic torque measurements are reported in a layered organic superconductor, β"-(BEDT-TTF)4[(H3O)Ga(C2O4)3]C6H5NO2 with Tc=4.8 K, where BEDT-TTF stands for bis(ethylenedithio)tetrathiafulvalene. Because of the large anion between the BEDT-TTF conducting layers, the superconductivity of this salt is highly anisotropic. In magnetic fields parallel to the conducting layers for T = 0.4 K, the magnetic torque shows a large diamagnetic signal associated with hysteresis up to ∼21 T, suggesting the up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 38 publications
2
26
0
Order By: Relevance
“…The highly conducting in-plane channel is also suggested from the quantum oscillation study, in which a clear Shubnikov-de Haas oscillation was observed even in the CO state, where resistivity shows a semiconducting temperature dependence [19,26]. Observation of the Fulde-Ferrell-Larkin-Ovchinnikov superconducting state in high magnetic fields is more evidence of a clean electronic state in the conducting plane [27].…”
Section: Figmentioning
confidence: 68%
“…The highly conducting in-plane channel is also suggested from the quantum oscillation study, in which a clear Shubnikov-de Haas oscillation was observed even in the CO state, where resistivity shows a semiconducting temperature dependence [19,26]. Observation of the Fulde-Ferrell-Larkin-Ovchinnikov superconducting state in high magnetic fields is more evidence of a clean electronic state in the conducting plane [27].…”
Section: Figmentioning
confidence: 68%
“…If the commensurate condition is satisfied at some different fields, we could observe periodic oscillatory behavior of the interlayer resistance as the field increases, which is called commensurability (CM) effect. The CM effect was first theoretically predicted by Bulaevskii et al [22] Although FFLO phases have been investigated in various layered organic superconductors, the CM effect is experimentally observed only in the FFLO phases of λ-(BETS) 2 FeCl 4 [13] and β ′′ - [20] When the field is tilted from the layers, the oscillatory behavior disappears, which shows that the FFLO phase is easily broken by the orbital effect. From the CM conditions, λ FFLO is estimated to range from 20 nm to 150 nm.…”
Section: Introductionmentioning
confidence: 96%
“…[5][6][7][8] After that, a FFLO phase transition has been found in λ-(BETS) 2 X (X = GaCl 4 , FeCl 4 ), [9][10][11][12][13][14][15] β"-SF 5 , [16][17][18][19] and β"-(BEDT-TTF) 4 [(H 3 O)Ga(C 2 O 4 ) 3 ]C 6 H 5 NO 2 . [20] In highly two dimensional (2D) superconductors, magnetic flux lines can be decomposed into two parts, pancake vortices (PVs) in the SC layers and Josephson vortices (JVs) in the insulating layers between the SC layers. In contrast to PVs, JVs have no normal cores, and thus JVs are pinned very weakly: JVs are easily driven by a perpendicular current.…”
Section: Introductionmentioning
confidence: 99%
“…There indeed have been a number of studies for such field orientation reporting evidence for the existence of FFLO states in these 2D organic superconductors. These claims were mainly based on transport data, such as on thermal-conductivity [31], interplane-resistance [32,33], and penetration-depth measurements [34][35][36]. Clear thermodynamic and microscopic evidence for a high-field FFLO phase was missing until 2011.…”
Section: Fflo Evidence In Layered Organic Superconductorsmentioning
confidence: 99%